Combined Oral Administration of GABA and DPP-4 Inhibitor Prevents Beta Cell Damage and Promotes Beta Cell Regeneration in Mice - Liu, Wenjuan; Son, Dong Ok; Lau, Harry K.; Zhou, Yinghui; Prud’homme, Gerald J.; Jin, Tianru; Wang, Qinghua (Frontiers in Pharmacology, 2017)
γ-aminobutyric acid (GABA) or glucagon-like peptide-1 (GLP-1) based drugs, such as sitagliptin (a dipeptidyl peptidase-4 inhibitor), were shown to induce beta cell regenerative effects in various diabetic mouse models. We propose that their combined administration can bring forth an additive therapeutic effect. We tested this hypothesis in a multiple low-dose streptozotocin (STZ)-induced beta cell injury mouse model (MDSD). Male C57BL/6J mice were assigned randomly into four groups: non-treatment diabetic control, GABA, sitagliptin, or GABA plus sitagliptin. Oral drug administration was initiated one week before STZ injection and maintained for six weeks. GABA or sitagliptin administration decreased ambient blood glucose levels and improved the glucose excursion rate. This was associated with elevated plasma insulin and reduced plasma glucagon levels. Importantly, combined use of GABA and sitagliptin significantly enhanced these effects as compared with each of the monotherapies. An additive effect on reducing water consumption was also observed. Immunohistochemical analyses revealed that combined GABA and sitagliptin therapy was superior in increasing beta cell mass, associated with increased small-size islet numbers, Ki67+ and PDX-1+ beta cell counts; and reduced Tunel+ beta cell counts. Thus, beta cell proliferation was increased, whereas apoptosis was reduced. We also noticed a suppressive effect of GABA or sitagliptin on alpha cell mass, which was not significantly altered by combining the two agents. Although either GABA or sitagliptin administration delays the onset of MDSD, our study indicates that combined use of them produces superior therapeutic outcomes. This is likely due to an amelioration of beta cell proliferation and a decrease of beta cell apoptosis.